Development of E-Modules Based on Pugers Marine Potential to Improve Higher Order Thinking Skills in Junior High School - Wahyuni*, Sri; Putri, Alifiah; Fadilah, Rizka Elan; Sya'adah, Himatus (Jurnal IPA & Pembelajaran IPA, 2025)
This study focuses on the development of an e-module for science learning based on the advantages of Puger's marine potential. Development of e-module is based on the need for Higher Order Thinking Skills-oriented and contextual teaching materials involving the students' surroundings which are expected to be able to improve students' HOTS. The purpose of this study is to examine the validity, practicality, and effectiveness of the e-module. This study is a Research and Development (RD) study using the ADDIE research model. Location of this research is at SMP Negeri 2 Puger with subjects of class VII B students in the 2024/2025 academic year. Research data were obtained from filling out validation sheets, observation sheets for learning implementation, student response questionnaires, and pre-tests and post-tests. Results of the research analysis show that (1) the percentage of validity of e-module science learning based on the marine potential of Puger is 95% with the criteria of very valid, (2) percentage of practicality of using e-module is 89.6% with the criteria of very practical, (3) the effectiveness of using the e-module shows an N-gain value of 0.702 with a high category, so it can be concluded that the science learning e-module based on marine potential of Puger is valid, practical, and effective in increasing the Higher Order Thinking Skills for junior high school students.